2008
DOI: 10.1111/j.1751-5823.2008.00044.x
|View full text |Cite
|
Sign up to set email alerts
|

Stationary‐Increment Variance‐Gamma and t Models: Simulation and Parameter Estimation

Abstract: Summary We detail a method of simulating data from long range dependent processes with variance‐gamma or t distributed increments, test various estimation procedures [method of moments (MOM), product‐density maximum likelihood (PMLE), non‐standard minimumχ2and empirical characteristic function estimation] on the data, and assess the performance of each. The investigation is motivated by the apparent poor performance of the MOM technique using real data (Tjetjep & Seneta, 2006); and the need to assess the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 15 publications
6
56
0
1
Order By: Relevance
“…Observe, in the first scatterplot, the sharp and negative posterior correlation between α and τ , as expected by Equation (3). Furthermore, the e-values for the hypotheses α 0 = −0.5 and α 0 = 0 are clearly zero, as confirmed by both graphs.…”
Section: Earthquake Acceleration Datasupporting
confidence: 71%
See 2 more Smart Citations
“…Observe, in the first scatterplot, the sharp and negative posterior correlation between α and τ , as expected by Equation (3). Furthermore, the e-values for the hypotheses α 0 = −0.5 and α 0 = 0 are clearly zero, as confirmed by both graphs.…”
Section: Earthquake Acceleration Datasupporting
confidence: 71%
“…It is worth noting the symmetry of the sampling distribution of the posterior mean for µ, as well as the asymmetry of the sampling distribution of the posterior mean for τ , as it was supposed to be by Equation (3). Furthermore, the estimates are consistent around the nominal value.…”
Section: Simulated Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Following Cont and Tankov (2004), there are two main approaches: the method of moments (MoM) and the maximum likelihood estimation. Recently, Finlay and Seneta (2008) have shown that the minimum χ 2 procedure produces an acceptable approximation of the marginal distribution in connection with a low calculation time. The χ 2 procedure corresponds to the goodness-of-fit test of the same name and tries to minimize the squared difference between observed absolute frequency and the number of observations derived from the theoretical probability.…”
Section: Fitting the Parametersmentioning
confidence: 99%
“…According to Finlay and Seneta (2008), we split the data set into 100 equal-sized sample bands. Owing to the different time series, we fitted the overnight parameters (c ON , θ ON , κ ON , σ ON ) and the intraday parameters (c ID , θ ID , κ ID , σ ID ) separately (for example, the dot at c stands for either ON or ID) ( Table 1).…”
Section: Fitting the Parametersmentioning
confidence: 99%